Indian politics: a study of people's involvements - "Panda, Snehalata" (New Delhi, 1988)
Here is a study on some aspects of India's political behaviour. Of parti cular interest are the socio-political changes and challenges to nation building and the role that castes and classes are playing. Involvement in politics is conditioned by the society and the psyche of the individual. But independent variables are lacking. The responsibility of nation building also lies equally on the bureaucracy and political leaderships but there is in sight a cleavage between the two, adversely affecting the growth of democracy. The book seeks to suggest ways and means for reformation.
Keywords: Politics- India